2020
DOI: 10.2174/0929867326666190328151539
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota, Immune System and Autism Spectrum Disorders: An Integrative Model towards Novel Treatment Options

Abstract: Background: Autism spectrum disorder (ASD) is a condition strongly associated with genetic predisposition and familial aggregation. Among ASD patients different levels of symptoms severity are detectable, while the presence of intermediate autism phenotypes in close relatives of ASD probands is also known in literature. Recently, increasing attention has been paid to environmental factors that might play a role in modulating the relationship between genomic risk and development and severity of ASD. Within this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(84 citation statements)
references
References 171 publications
7
77
0
Order By: Relevance
“…In both ASD and BS, involvement of the immune system has been hypothesized. For example, dysregulation of immune function and neuroinflammation, as well as the presence of maternal autoantibodies directed against fetal brain tissue, have been involved in the pathophysiology of ASD [19,21]. Recently, some authors highlighted the potential role of maternal antibodies against stress-induced phosphoprotein 1 (STIP1) [51], a ligand of prion protein found in the developing brain that has been shown to mediate neurogenesis in cultured hippocampal neurons [52,53].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In both ASD and BS, involvement of the immune system has been hypothesized. For example, dysregulation of immune function and neuroinflammation, as well as the presence of maternal autoantibodies directed against fetal brain tissue, have been involved in the pathophysiology of ASD [19,21]. Recently, some authors highlighted the potential role of maternal antibodies against stress-induced phosphoprotein 1 (STIP1) [51], a ligand of prion protein found in the developing brain that has been shown to mediate neurogenesis in cultured hippocampal neurons [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, increasing literature highlighted several kinds of immune system alterations, such as altered levels of cytokines, in patients with ASD [57]. The authors suggested the presence of shared genetic underpinnings between ASD and autoimmune diseases, which would interact with early environmental factors, in particular during intrauterine life, in shaping neuroimmune patterns [19,21]. On the other hand, also AN has been linked with the presence of immune system alterations: while some authors stressed the presence of a higher vulnerability of patients with autoimmune diseases towards the development of AN, pointing out a possible role of the immune system in the pathogenesis of eating disorders [58], others highlighted the presence of immune system dysregulation in patients with AN, hypothesizing that it may be caused by the altered nutritional status [59].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations